Leverage Influence,Company Size and Corporate Governance on Company Performance in the Mining Sector 2016-2019 - Deny Martin; Syahputra Syahputra; Rico Tanoto; Erwin Gantedy; Chori Aditya Pallas (Institute of Computer Science (IOCS), 2021)
This research was conducted to determine and examine the effect of leverage ratios, company size and corporate governance on the performance of mining sector companies for the 2016-2019 period. This research is a deductive, quantitative and descriptive research that uses secondary data from financial reports obtained from the financial statements of the mining sector. For data processing using multiple linear regression analysis techniques. The results of the research findings individually that the leverage ratio has negative implications for company performance, corporate governance has positive implications for financial performance and company size has no impact on financial performance. Simultaneous research results show that the leverage ratio, company size and corporate governance have implications for financial performance of 20.2%.